Гистогенез скелетных мышц пресмыкающихся и некоторые вопросы эволюции миогенеза амниот - Борисов, И.Н. (Вестник зоологии, 1970)
The growing point and material of dermatome are the sources of Reptilia body muscles. After disappearance of the cambium zones, a number of muscular fibres increases by means of longitudinal delamination of the available fibres. The comparison ol myogenesis of reptiles, birds and mammals shows, that during the transition from reptiles to birds and mammals the muscular fibre delamination becomes more intensive and occurs at earlier stages of myogenesis, which results in its desynchronization. In some mammals this desynchronization is overcome owing to the division of the period of muscular fibre delamination into two waves.